The use of technology enhanced learning in health research capacity development: lessons from a cross country research partnership. Issue 1 (December 2016) - Byrne, E.; Donaldson, L.; Manda-Taylor, L.; Brugha, R.; Matthews, A.; MacDonald, S.; Mwapasa, V.; Petersen, M.; Walsh, A.
Abstract Background With the recognition of the need for research capacity strengthening for advancing health and development, this research capacity article explores the use of technology enhanced learning in the delivery of a collaborative postgraduate blended Master's degree in Malawi. Two research questions are addressed: (i) Can technology enhanced learning be used to develop health research capacity?, and: (ii) How can learning content be designed that is transferrable across different contexts? Methods An explanatory sequential mixed methods design was adopted for the evaluation of technology enhanced learning in the Masters programme. A number of online surveys were administered, student participation in online activities monitored and an independent evaluation of the programme conducted. Results Remote collaboration and engagement are paramount in the design of a blended learning programme and support was needed for selecting the most appropriate technical tools. Internet access proved problematic despite developing the content around low bandwidth availability and training was required for students and teachers/trainers on the tools used. Varying degrees of engagement with the tools used was recorded, and the support of a learning technologist was needed to navigate through challenges faced. Conclusion Capacity can be built in health research through blended learning programmes. In relation to transferability, the support required institutionally for technology enhanced learning needs to be conceptualised differently from support for face-to-face teaching. Additionally, differences in pedagogical approaches and styles between institutions, as well as existing social norms and values around communication, need to be embedded in the content development if the material is to be used beyond the pilot resource-intensive phase of a project.